Can We Explain Differences in Patterns of Alcohol Consumption? Review of Theoretical Approaches - Valeria Kondratenko; Yana Roschina (Journal of Economic Sociology, 2021)
Alcohol is an important part of the culture of many people, and the patterns of its consumption differ according to the types of drinks people drink, in what circumstances they drink, what kind of meaning drinking offers them, etc. In this article, we decided to classify publications on differences in drinking patterns based on a dominant idea. We highlight the criteria for identifying such patterns: quantitative (depending on the volume and frequency of consumption) and qualitative (depending on the chosen drinks, circumstances, and motives for use). The quantitative criteria make it possible to identify frequently used patterns, such as episodic alcohol consumption in large quantities, binge drinking, sporadic drinking, and light and heavy drinking. Within the framework of the qualitative criteria, Northern, Southern, and Central European types are often distinguished. The emphasis on consumption motives reveals four patterns: reinforcement, coping, conformity, and community. However, researchers tend to understand what explains the differences in consumption patterns. Therefore, in the second part of the article, we turn to the systematization of such explanations based on cultural-anthropological, historical, and structural approaches. In the last part of our article, we show that the approaches we have identified allow us to explain the features of alcohol consumption patterns in Russia and their changes over the past several decades. It can be concluded that the most productive way of analyzing alcohol consumption is the complex application of the approaches we have considered—the identification of patterns based on various criteria and the explanation of their choice by different highlighted approaches.